Implementation of Character Education Based on Islamic Values at Madrasah Tsanawiyah - Fahrurrozi Fahrurrozi; Mujamil Qomar; Sokip Sokip (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to describe the implementation of character education based on Islamic values at Madrasah Tsanawiyah Al-Makrif Kereak using a qualitative approach that emphasizes data obtained from interviews and observations. The focus of this research includes the strategies employed by teachers to instill Islamic values, the roles of the principal and educational staff, and the identification of Islamic values integrated into character education. The findings reveal that religious studies teachers apply contextual learning strategies and group discussions to instill Islamic values in students' daily lives. This approach not only enhances students' cognitive understanding but also fosters deep emotional and social engagement. The principal and educational staff play a crucial role in supporting the implementation through teacher training, integration of Islamic values across various subjects, and the organization of extracurricular activities grounded in Islamic principles. Key values integrated include honesty, responsibility, discipline, and compassion. These values are applied through learning processes, religious practices, and social interactions among students, and have shown a positive impact on students’ attitudes and character